A Phosphorus Analogue of Acenaphthylene. Issue 38 (7th August 2017) - Huang, Haiyang; Wei, Zhibin; Wang, Mincan; Duan, Zheng; Mathey, François
Abstract : A 1‐phosphaacenaphthylene has been obtained by the deprotonation and collapse of the phosphorus bridge of an appropriate 7‐phosphanorbornenium salt. DFT computations showed that the molecule has an elongated P=C double bond of 1.736 Å with a strained C–P=C angle of 88.9°. The P lone pair corresponds to the HOMO–2. Its complexation by [W(CO)5 ] or AuCl induced a clean addition of methanol and water to the P=C double bond. The water addition product was characterized by X‐ray crystal structure analysis. Abstract : The conversion of a λ 5 ‐P‐ylide into a λ 3 ‐phosphaalkene provides the first example of a 1‐phosphaacenaphthylene derivative.